Implementasi Pengering Tepung Aci Di UMKM Mi Aci Pakde Sugeng Tiyuh Pulung Kencana Tulang Bawang Barat - Subeki; Gusri Akhyar; Arinal Hamni; Lusmeilia Afriani; Dewi Sartika; hamimatun Niswah (JITER-PM (Jurnal Inovasi Terapan - Pengabdian Masyarakat), 2024)
Cassava flour or tapioca flour is one of the types of cassava products that has been widely developed as the main raw material for producing wet tapioca noodles. The village of Pulung Kencana in West Tulang Bawang Regency has local wisdom in the form of processed food products, such as tapioca noodles produced from cassava flour. Cassava flour is obtained from the result of tapioca or the sediment of grated cassava, which is dried for some time until it reaches a moisture content of 12%. The drying process is done naturally and highly depends on sunlight, sometimes hindered during periods without heat. Therefore, a drying tool is created using a homemade heater fueled by gas or firewood. The hot air in the pipe is blown into the drying chamber, which functions to dry the flour placed in tiers. The air moves from the bottom to the higher racks, allowing the heat to be used gradually. The drying chamber's capacity can dry 30 kg in one drying session, within 8 hours, achieving a moisture content of 12%. When using LPG, it requires 8 hours. The drying results show that the moisture content is 12%, meeting the required conditions